Front Cover: Synthesis of a Cu2O/Carbon Film/NiCoB‐Graphene Oxide Heterostructure as Photocathode for Photoelectrochemical Water Splitting (ChemElectroChem 7/2019). Issue 7 (6th March 2019) - Yu, Chunlin; Zhang, Xingwang
Abstract : The Front Cover shows a creative Cu2 O/Carbon film /NiCoB‐GO heterostructure photocathode for enhanced PEC water splitting. The resultant photocathode shows the efficient carrier separation by the successfully construction of electron transport path. This research provides a novel heterostructure for enhancing PEC performance. More information can be found in the Article by C. Yu and X. Zhang onpage 2004 in Issue 7, 2019 (DOI:10.1002/celc.201801701 ).